Formulation and Activity Test of Grapefruit Peel Extract Anti-Acne Gel Preparation (Citrus maxima Merr.) Against Staphylococcus aureus and Propionibacterium acne Bacteries - Latu, Saparuddin; Jangga; Suleman, Abdul Wahid; Putri, Hardyanti Eka; Herman, Sriyana; Mahmudah, Rifa’atul; Rusli; Nurhikmah (YCAB Publisher, 2025)
Background: Grapefruit (Citrus maxima Merr.) peel is known to contain bioactive compounds such as alkaloids, tannins, and flavonoids, which exhibit potential antibacterial properties, particularly against acne-causing bacteria.Objective: This study aimed to formulate an anti-acne gel incorporating grapefruit peel extract, evaluate its antibacterial activity against Staphylococcus aureus (SA) and Propionibacterium acnes (PA), and determine the optimal extract concentration for inhibiting bacterial growth.Methods: A laboratory-based experimental study was conducted using the well diffusion (pitting) method to assess antibacterial activity. Gel formulations containing grapefruit peel extract at concentrations of 5%, 10%, and 15% were tested against SA and PA.Results: The formulated gels demonstrated acceptable physical stability. The inhibition zones against SA were as follows: 5% (F1) = 10.2 mm, 10% (F2) = 11.2 mm, and 15% (F3) = 11.1 mm. Against PA, the inhibition zones were: F1 = 11.7 mm, F2 = 13.3 mm, and F3 = 11.7 mm. The 10% formulation (F2) exhibited the highest antibacterial activity against both bacterial strains, falling within the